معالم التجديد في الخطاب الديني بين الواقع والمأمول: Milestones of Al-Tajdid in Religious Discourse Between Reality and Hope - Abdul Mukit; Abdul Salam Hamood Ghaleb Alanesi (Universitas Darussalam Gontor, 2025)
Tajdid in religious discourse has become a prominent and open topic for its proponents. Therefore, there is a need to actively engage with the contemporary world while remaining rooted in tradition. This entails innovation in both methods and themes. It is crucial to clarify the concept of religious discourse and renew it within established boundaries. The researcher employed the inductive and descriptive-analytical approach to address the subject. This renewal maintains a commitment to faith, respects divine revelation, values reason, and considers human nature and instincts. It is a discourse that calls for spirituality without neglecting material aspects, promotes tolerance and love, appeals through exemplary conduct without ignoring reality, and acknowledges human ability and fallibility. It encourages diligence yet does not overlook the need for relaxation, supports contemporaneity while upholding tradition, preserving the essence of the old while embracing beneficial aspects of the new. Renewal does not entail a rejection of the past or the abandonment of core principles; rather, it involves the consistency of goals with the evolution of methods. This approach embraces facilitation in legal verdicts, optimism in outreach, equity towards women without injustice to men, and the protection of majority rights without infringing on those of minorities.